PENGARUH PENGALAMAN AUDITOR, INDEPENDENSI DAN BEBAN KERJA TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI FRAUD - Annisa Bella Mariyana (2021)
This research aims to determine the effect of auditor experience, independence, and workload on the auditor's ability to detect fraud. The population in this research is an auditor who work in Public Accounting Firm in South Jakarta area. Sampling was conducted used convenience sampling methods which produced 67 samples of auditors. Data analysis used in this research is multiple linier regression with 5% significant level with SPSS version 23. This result on this research show that (1) Auditor Experience has no significant effect on the auditor's ability to detect fraud, (2) Independence has significant effect on the auditor's ability to detect fraud, (3) Workload has significant effect on the auditor's ability to detect fraud.